Fallen idols twelve statues that made history - Von Tunzelmann, Alex 1977- (Harper, an imprint of HarperCollins Publishers, 2021)
In 2020, history came tumbling down. But as the past three hundred years have shown, history is not erased when statues are removed. Exploring the rise and fall of twelve famous, yet now controversial statues, Alex von Tunzelmann takes us on a fascinating global historical tour filled with larger than life characters and dramatic stories. Von Tunzelmann reveals that statues are not historical records but political statements and distinguishes between statuary and other forms of sculpture, public art, and memorialization
Originally published in the UK in 2021 by Headline Publishing Group
Keywords: Kontroverse; Denkmal; Historische Persönlichkeit; Geschichtsbewusstsein; Öffentlicher Raum; Sculpture / History; Sculpture / Social aspects; Statues / History; Statues / Social aspects; Statues / Moral and ethical aspects; Monuments / History; Monuments / Social aspects; Monuments / Moral and ethical aspects; Collective memory; Pop art / Social aspects; Arts and society; Monuments; Sculpture; Statues; Informational works; History